Zloraba moči in nasilje v medosebnih razmerjih - Rakovec-Felser, Zlatka (Obzornik zdravstvene nege, 2009)
The importance of adequate communication, knowledge of its nature and structure is indisputable, especially so in the health care system as can it can contribute to better interactions between health providers and patients and enhance the client's compliance during diagnostic and therapeutic procedures. The article focuses on the abuse of power, behavior patterns of physical and psychological violence in interpersonal relationships by outlining in theoretical terms the interpersonal communication, life roles and interactive relationships. Presented in the paper are different forms of power misuse, behavior patterns of physical and psychological violence as well as their cyclic processes and their psycho-social causes. Abuse and violence in family settings are highlighted as they are statistically significant and serious in spite of common idealizations of safe parental/family milieu. The article concludes with some guidelines for early recognition of torture victim status and intervention.
Keywords: Child Abuse; družina; family; Interpersonal Relations; Medosebna razmerja; medosebni odnosi; moč; Moč (psihologija); Nasilje; power; Power (Psychology); Spouse Abuse; Violence; Zakonec, zloraba; zloraba; Zloraba otrok